Design of Personalized Blended Learning Environments Based On Web-Assisted Modelling In Science Education - Murat Çetinkaya (International Journal of Evaluation and Research in Education (IJERE), 2016)
Positive results of science teaching studies supported with the means provided by technology require the enrichment of the content of blended learning environments to provide more benefits. Within this context, it is thought that preparing a web-assisted model-based teaching, which is frequently used in science teaching, based on the “Matter and Heat” unit will be useful. A great number of studies on “Matter and Heat” unit have reported that many students have conceptual errors. It has been found that students have difficulties in associating concepts such as matter, heat, temperature and change of state with daily life. Studies have shown the necessity of designing and using effective teaching methods in solving such problems. It is thought that the modeling based web materials developed for the unit of matter and heat will be effective in decreasing students’ conceptual errors and their learning difficulties. ASSURE teaching design model, which aims to increase the efficiency of material choice and use with systematic prior planning of teaching, was used in creating the materials which were prepared based on web-assisted modeling. The purpose of this study is to design of personalized blended learning environments which are designed based on web-assisted modeling for “Matter and Heat” unit.